Clean up with COSHH 2000 : a TUC guide to the Control of substances hazardous to health Regulations 1999 and COSHH essentials (London, 2000)
"This guide to the Control of Substances Hazardous to Health Regulations 1999 (and COSHH essentials) will interest union safety reps in a range of industries where chemical illness in the workplace is a problem or a threat. The guide gives an overview of hazardous substances and outlines legal standards. The sister course book on COSHH is already available to reps attending TUC health and safety education courses."